Rómulo Gallegos in front of the Venezuelan plain: Sound panoramas in Doña Bárbara - Kube Tamayo, Luciana (2021)
This paper analyzes the environmental sound in the Venezuela’s plain at the end of 1920 in the novel Doña Bárbara by Rómulo Gallegos, according to the soundscape concept (M. Schafer).